Managing Records and Information for Transparent, Accountable, and Inclusive Governance in the Digital Environment : Lessons from Nordic Countries - Thurston, Anne (World Bank, Washington, DC, 2015)
This set of three case studies explores the intersection of openness, digital governance, andhigh quality information in Estonia,1 Finland, and Norway with the aim of identifying lessonsthat will support the same objectives in lower resource countries. Openness, a key aspect ofthe international agenda for increasing transparency and accountability, for reducing public sectorcorruption, and for strengthening economic performance, rests on the principle that citizenshave a right to know what their governments are doing and to benefit from using governmentinformation. Goals for open, accountable, and inclusive governance rest on the assumption thattrustworthy information is available and can be shared meaningfully through strategies for digitalgovernance. This assumption needs to be examined. Does reliable and complete informationexist across lower resource countries? Can it be accessed readily? Will it survive through time?